Aktivitas Fisik, Gaya Hidup Sedenter dengan Status Gizi Anak Sekolah Dasar: Systematic Review - Cicih, Lilis Heri Mis; Anggraini, Hesty Riana; Chairunnisa, Icha; Indriyati, Titi; Djaali, Nur Asniati; Pustikasari, Atikah (Universitas Mohammad Husni Thamrin, 2023)
Physical inactivity and sedentary lifestyle contribute to a person's nutritional status. Nutritional problems, especially in children, can affect the quality of human resources in the future. To analyze the relationship between Physical Activity and Sedentary Lifestyle with Nutritional Status. The study method used was systematic review. Literature was obtained from the database, Google Scholar, 27,900 articles were obtained and 7 of them were in accordance with the study objectives. The results of the review showed that physical activity and sedentary lifestyle have no relationship with the nutritional status of elementary school-age children. Recommendation: Nutritional problems, especially in children, can affect the quality of human resources in the future, so it is hoped that parents can pay more attention and encourage children to have a healthy lifestyle by doing regular physical activity and reducing sedentary lifestyles. It is expected that schools can also campaign for nutrition education programs and provide facilities to support physical activity in the school environment.